The Treatment of Landfill Leachate by Electrocoagulation to Reduce Heavy Metals and Ammonia-Nitrogen - Kasmuri, Norhafezah; Aliah Ahmad Tarmizi, Nur; ., . (International Journal of Engineering and Technology, 2018)
Landfill leachate contains high concentration of contaminants in the form of nitrogen, suspended solids and heavy metals, which effects the environment adversely.Â Hence leachate treatment is considered vital in landfill management as the effluent needs to undergo several treatments before being discharged into natural water bodies.Â Without treatment, the leachate will contaminate the surface and ground water as it can penetrate through soils and subsoils. Several methods have been applied for the treatment of landfill leachate. However, these methods have several constraints due to area required and cost incurred. This paper presents the application of electrocoagulation in removing pollutants from landfill leachate; particularly ammonia-nitrogen and heavy metals.Â Three metals namely aluminium, iron and zinc were used as electrodes.Â Aluminium electrode was found to be the most effective where it was capable to extract 89% of zinc and 75% of iron in 30-minute retention time.Â Â Subsequently, 93% of zinc and 83% of iron was removed in 120 minutes.Â In addition, 93% of ammonia-nitrogen was also removed.Â Â These results led to a conclusion that the electrocoagulation had the capacity to remove heavy metals and ammonia-nitrogen present in landfill leachate.Â Â Â Â